Characterization of the Role of Herpes Simplex Virus protein VP 16 in Viral Gene Expression through Interactions with the Virion Host Shutoff protein (vhs) and HCF-1 - Knez, Jozo (My University, 2003)
Herpes Simplex Virus 1 (HSV1) VP16 transcriptionally activates viral immediate-early (IE) genes, through the formation of a multi-protein structure termed the VP16-induced complex (VIC). VIC is comprised of cellular transcription factors Oct -1 and HCF-l. In addition, VP 16 is a pre-formed, structural protein that has a critical role in virion assembly. At least one aspect of its role at late times post-infection includes the downregulation of the virion host shutoff protein (vhs); which functions to indiscriminately degrade mRNA. The interaction between VP 16 and vhs was characterized within this thesis in order to differentiate it from the regions involved in VIC assembly, as well as to investigate its functional importance within HSV 1. Refined mutagenesis studies were used to localize a minimal binding domain within VP16; in which the alteration a single residue was sufficient to abrogate binding to vhs. Our results indicate that the interaction between VP16 and vhs could effectively be uncoupled from VIC assembly and the transactivation of IE genes. Moreover, virus complementation assays were used to demonstrate that the interaction with vhs is specifically required to sustain virus growth. We were also interested in characterizing VP16 transactivation. Previous work within our laboratory had determined that the amino-terminal domain of VP16, excluding itspotent acidic activation domain (AAD), possessed an activation phenotype in yeast and mammalian cells. To investigate these findings further, mutagenesis experiments were employed to differentiate between the activity in mammalian and yeast cells. HCF-l, a recently identified transcriptional co-regulatory protein, was identified as a co-activator of the truncated VP 16 in mammalian cells. HCF-l was also capable of synergizing VP 16 in the activation of an IE gene construct. These findings identify a novel role for HCF-l in HSV 1 gene expression. Taken together, this work enhances our understanding of the role of VP 16 in viral gene expression and pathogenesis.
Keywords: Biochemistry; Biochemistry